2017
DOI: 10.1007/s00270-017-1564-x
|View full text |Cite
|
Sign up to set email alerts
|

Post-procedural Care in Interventional Radiology: What Every Interventional Radiologist Should Know—Part I: Standard Post-procedural Instructions and Follow-Up Care

Abstract: Interventional radiology (IR) has evolved into a full-fledged clinical specialty with attendant patient care responsibilities. Success in IR now requires development of a full clinical practice, including consultations, inpatient admitting privileges, and an outpatient clinic. In addition to technical excellence and innovation, maintaining a comprehensive practice is imperative for interventional radiologists to compete successfully for patients and referral bases. A structured approach to periprocedural care,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 78 publications
0
17
0
2
Order By: Relevance
“…Reviews in 2017 pointed that the antibiotics is necessary and beneficial even in the absence of risk of inflectional factors. 4 Other analysis of previous clinical trials, 5 pointed that the use of antibiotics may not be routinely necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Reviews in 2017 pointed that the antibiotics is necessary and beneficial even in the absence of risk of inflectional factors. 4 Other analysis of previous clinical trials, 5 pointed that the use of antibiotics may not be routinely necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Laflamme et al concluded that electronic note templates are superior to dictation services in improving both the efficiency and the comprehensiveness of perioperative documentation (Laflamme et al 2005 ). A further benefit of proforma use includes the reduction in reporting variability such that greater transparency is achieved when it comes to reimbursement of procedures (Taslakian and Sridhar 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…24 At a minimum, clear documentation with a postprocedure note, prompt procedure report, and written instructions for postprocedural care should be provided. 25 If a patient is being transferred outside of IR, an appropriate hand over to the receiving team should take place. 26…”
Section: Communication With Referring Clinical Teamsmentioning
confidence: 99%